Accountability For The Performance Of Palembang City Government Agencies Through An Institutional Isomorphism Theory Approach - Bolley, Stevy Josephin; Desi Indriasari; Meilinda Dwi Anugrah (Universitas Lancang Kuning, 2025)
This study identifies a research gap between the implementation of reporting systems, e-budgeting, and performance-based budgeting and The degree of accountability for performance within the Palembang City Government. Although the city has achieved a